Situasi Pendidikan Islam di Indonesia Pasca Masa Pandemi Covid-19 - Fitri Nurjannah (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2022)
Islamic education in Indonesia seems to be full of problems, this started from the colonial period to the current post-reform. Setbacks and backwardness have also been recognized in the reality of Islamic education. The year 2020 is a year that can be called a gray year for Islamic education in Indonesia. Islamic education becomes less relevant to student learning outcomes, because there is no learning model that is suitable for student brain performance. With the occurrence of this COVID-19 pandemic, it has indirectly changed the order of Islamic education which has been running comfortably so far. The existence of a Work From Home (WFH) policy, social and physical distancing, as well as an online or online system in the process of Teaching and Learning Activities (KBM), also enliven the course of Islamic education in Indonesia today. Learning that was originally carried out offline or face to face, has turned online and is carried out at home. This study attempts to briefly re-explain the situation of Islamic education in post-reform Indonesia in the current pandemic era.